Economic paradigms, socio-environmental emergency and territorialization processes in biological corridors in Villavicencio 1980-2015 (Revista "Boletín el Conuco", 2022)
This research work analyzes the developmental model of production together with its environmental effects resulting from the different economic models in the period 1980 to 2015. It is, in turn, the result of the analysis and study of the territorial pressures emanating from the 1950s of the 20th century have been exerted on the surrounding area of ​​the Zuria biological corridor in Villavicencio, and have generated a decrease in the forest canopy and loss of biodiversity in the sector. This list of environmental issues linked to practices derived from the developmental model of production, are focused on answering the central research question on how social actors, through their socioeconomic activities and their socioenvironmental perspectives, have reconfigured the territory forming a border socio-environmental in the biological corridor Zuria, Villavicencio in the period 1980-2015? To this end, a descriptive analytical qualitative research methodology was incorporated, since precisely this type of research can take a starting point or go back in it until finding the connections between already known or evident facts. This is how it was concluded that the social actors that live there have carried out social and economic practices, consistent with the development model, which have decimated the flora and fauna of the Zuria biological corridor, and which in turn are incompatible with the land use.